PERAN HUMAS DALAM MENINGKATKAN MUTU PENDIDIKAN ISLAM DI SMA SWASTA WIDYA DHARMA PT. ASAM JAWA KAB. LABUHANBATU SELATAN - Afriandika Ritonga; M. Yoserizal Saragih (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2022)
The role of public relations in an institution or organization is very important, because every institution requires the performance of a public relations officer to help run work programs, and public relations can also maintain the image of an institution, so that an institution can be recognized and trusted by the public with a public relations strategy. This research, when viewed from the location of the data source, belongs to the category of field research (field research). Data collection techniques used participant observation and in-depth interviews. The results of this study indicate that: 1) The role of public relations in improving the quality of education through internal and external activities. 2) The contribution of public relations in improving the quality of education has the advantage of covering activities in schools such as infaq, cleanliness, religion and home visits that have a positive and mutually beneficial impact. 3) Weaknesses in schools include: time, finances, the role of parents, textbooks and the environment.